Islam : its beginnings and history, its theology and its importance today - Crotty, Robert B.; Lovat, Terry (ATF Press, 2016)
Terrorism is the threat of the age, or so we are told, and inevitably associated with it is the word 'Islam'. The notion of the 'Muslim terrorist' has become a colloquialism in Western media. Interestingly, in all the history books about the Second World War, the phrase 'Christian fascist' is rarely seen in spite of the fact that skewed Christian theologies were used liberally by the Nazis to further their hatred. This points to a blind spot in Western understanding about the ways in which religious (and non-religious) ideology can be mutilated to serve hateful ends. We think we see it in Isla.